Legal Protection for Gojek Drivers Against Fictitious Orders with Cash On Delivery Payment - Aulia Raihan (Proceedings Series on Social Sciences & Humanities, 2023)
Transportation and humans are two things that cannot be separated. Currently, people often use transportation services with an online system in the form of applications on smartphones, especially Gojek. One of the Gojek services is the existence of food delivery services or Gofood, this service makes it very easy for consumers who cannot buy food directly. However, when doing their job it is not uncommon for the driver to experience losses, especially during cash on delivery transactions. This is due to fictitious orders by irresponsible consumers which can cause losses to drivers. Based on this background, this paper raises the following problem formulations a) How is legal protection for gojek drivers against fictitious orders with cash on delivery payments? b) How is the form of corporate liability of PT Gojek Indonesia for gojek drivers against fictitious orders with cash on delivery payments? The type of research used is normative juridical research, namely research that examines statutory provisions. Legal research uses various approaches with the aim of obtaining information from various aspects of the problem under study. The results of this study are that the legal protection of gojek partners for GoFood fictitious orders made by consumers is still not optimal. However, referring to article 1267 KUHPer gojek partners get legal protection when consumers make fictitious order actions, on the other hand these consumers have violated article 5 point (b) of Law Number 8 Year 1999 concerning Consumer Protection. PT Gojek Indonesia provides compensation in the form of a full refund in accordance with the loss of fictitious orders experienced by gojek drivers as a form of PT Gojek Indonesia's responsibility with its partners. The compensation process can be claimed by the customer to the Gojek Indonesia company with the loss claim procedure as determined by PT Gojek Indonesia. Submission of compensation claims can be submitted to the Branch Office of the gojek driver's operational area.